2010
DOI: 10.1007/s11126-010-9124-4
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Evidence-Based Interventions to Fit Usual Practice: Staff Roles and Consumer Choice in Psychiatric Rehabilitation

Abstract: This proof-of-concept study tested the viability of adapting a specialized practice to fit multi-service programs by switching from specialist to generalist staff roles. The intervention under study was supported employment, an evidence-based practice for adults with severe mental illness. Program data on participant characteristics, attendance, staff contact, and employment were retrieved for the 2007 calendar year (N = 99). Two hierarchical regression analyses compared (1) participants with any versus no mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…The results of this study are consistent with previous studies that have documented organizational (28)(29)(30)(31), provider-based (9,(32)(33)(34), and clientbased (9,35) barriers or constraints to the implementation of evidencebased treatments and practices. They are also consistent with previous studies that have focused on adaptations of evidence-based treatments to accommodate the needs of clients belonging to specific age (36) or racial-ethnic (37) groups, provider preferences (38), or organizational context (39).…”
Section: Reason Examplesupporting
confidence: 90%
“…The results of this study are consistent with previous studies that have documented organizational (28)(29)(30)(31), provider-based (9,(32)(33)(34), and clientbased (9,35) barriers or constraints to the implementation of evidencebased treatments and practices. They are also consistent with previous studies that have focused on adaptations of evidence-based treatments to accommodate the needs of clients belonging to specific age (36) or racial-ethnic (37) groups, provider preferences (38), or organizational context (39).…”
Section: Reason Examplesupporting
confidence: 90%
“…There have also been efforts to expand how IPS is done. For example, one study looked at expanding SE beyond the rigid requirements of IPS [67]. Instead of using specialized IPS delivery centers, these researchers were able to show that IPS can be effectively delivered in a ‘multi-server’ program center.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study of this same program demonstrated that SE services can be effectively provided by psychosocial program professionals practicing as generalists [53], and this program's 2008 and 2009 quarterly employment rates were similar to the quarterly rates reported for other SE programs [57], so it seems reasonable to recommend that psychosocial programs designed to promote both peer support and social integration add supported employment to their array of rehabilitation services.…”
Section: Resultsmentioning
confidence: 67%
“…The program is also open as a drop-in center on weekends. Job-hunting assistance and on-job support for Waverley Place members are provided primarily through one-on-one interactions with Waverley Place staff [53] One-on-one supported employment services include newspaper and internet searches, social networking for job leads and references, resume preparation, interview coaching and practice, job-related skill and travel training, and work-focused supportive counseling, including discussions of social security benefits, income budgeting, family expectations, time management, and job pressures. All program members are invited to join a weekly employment support group where they can share their own accomplishments and experiences, and gain insights and job information from other members.…”
Section: Program Descriptionmentioning
confidence: 99%